A social accounting matrix of the regional economy, 1982/83 - Hazell, Peter B. R.; Ramasamy, C.; Rajagoplan, V.; Bliven, Neal (International Food Policy Research Institute, 1991)
This chapter uses an estimated social accounting matrix (SAM) to provide a detailed quantitative description of the North Arcot study region in 1982/83. The SAM framework provides a consistent, comprehensive, and detailed picture of the transactions in an economy. Production activities, commodities, factors, government, households, and other institutions can all be accommodated, and the pattern in which incomes are distributed takes its place alongside the sources of income generation. The SAM also provides the basis for the construction of a model of the regional economy, as discussed in Chapter 8.